Representação feminina na Câmara de Vereadores de Fortaleza - Rios, Genílria de Almeida (2014)
This work analyzes women’s political participation at the Municipal Council of Fortaleza, Brazil, from 1989 to 2012 with the aim to understand how women build their political trajectories towards parliament, considering the elements that interfere in the political action of these women in power and the motions they propose throughout their terms. Based on data regarding their social origins and political trajectories, parliament members’ legislative production, and occupation of positions of power inside the Municipal Council, together with semi-structured interviews, it was possible to identify the existence of meaningful differences among the female parliament members studied. Their political capitals, the prioritized areas of action and the way they endorse demands coming from their electoral base. Results obtained demonstrate that over half of motions produced does not refer directly to social questions, which is partly due to the specific attributions of such a position and its legislative limits over themes of local interest. The majority of female politicians sought to approve legislation for social categories deemed vulnerable, such as children, youth, the elderly, the disabled, homosexuals and women as well. Upon identifying this public’s demands, they presented proposals mainly related to the areas of health, education, social care and the environment, making up a politics of care, which refers the roles traditionally given to women in the private sphere. However, the research carried out inside the Council demonstrates a shift in perspective considering the roles of women in the legislative. There is a double guiding principle regarding parliamentary activities: related to the social area, but also to discussions and positions of greater prestige, such as the occupation of Directing Table and the main technical commissions of the Council, as well as the interest to legislate on themes related to public administration and local economy, which are traditionally associated with predominance of men.